2019
DOI: 10.1002/osi2.1012
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal epignathus in the oral and pharyngeal regions: A case report

Abstract: Congenital teratoma that arises in the oropharyngeal region is called epignathus. Here, we report a case in which large epignathus extending from the pharynx to the oral cavity was resected. A female fetus was found to have a mass extending on her face to the pharyngeal region during a sonographic examination performed at 33 weeks’ gestation. On the 9th day after birth, the tumor extending from the left nostril (10 cm) was excised by the pediatric surgeons. The residual tumor protruded from the oral cavity day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
3
2
0
Order By: Relevance
“…The presence of the larger tumor was found during the ultrasound exam in the 34th week of pregnancy, similar to other reports 9,10,12,16,19 in which the diagnosis also occurred in the third trimester. Other studies 7,8,20,23 reported the presence of teratoma in the second trimester of pregnancy, and in some 2,14,15 , only after birth.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The presence of the larger tumor was found during the ultrasound exam in the 34th week of pregnancy, similar to other reports 9,10,12,16,19 in which the diagnosis also occurred in the third trimester. Other studies 7,8,20,23 reported the presence of teratoma in the second trimester of pregnancy, and in some 2,14,15 , only after birth.…”
Section: Discussionsupporting
confidence: 90%
“…Although congenital oropharyngeal teratomas are considered rare benign tumors, when present, they can cause several sequelae in the child's oral cavity, as observed in this case report, requiring long-term multidisciplinary follow-up to correct them. This clinical case has many similarities with others found in the literature 2,[6][7][8]10,11,[15][16][17][18][19] . Regarding gender, most studies reported the presence of oropharyngeal teratomas in female children.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations